Pendampingan Pengembangan Sistem Informasi Antrian Disabilitas Rumah Sakit Panti Waluyo Purworejo - Danny Sebastian; Kristian Adi Nugraha (Patria : Jurnal Pengabdian Kepada Masyarakat, 2021)
Every patient has the right to receive healthcare service. However, not everyone has equal access to these services. This problem is especially apparent in patients with disabilities. Duta Wacana Christian University’s Faculty of Information Technology is working alongside Panti Waluyo Hospital in Purworejo to build a priority queueing system for disabled patients. This system is expected to improve patient admission and queueing process. The proposed system consists of a website and a mobile application which has undergo 6 months of continuous development and online mentorship, starting from January 2020 up until June 2020.